Design and Implementation of a Scalable Battery Management System - Sathyamoorthi, Guhan Raj; Mubanda, Talemwa Semanda (My University, 2020)
Our society is facing significant challenges due to accelerated climatic change brought by increased carbon emissions (from cars, industries and power generation) leading to global warming. According to the 2018 Transport and Environment report on carbon emissions (CO2 EMISSIONS FROM CARS: the facts), the transport sector is Europe’s single biggest source of carbon emissions contributing 27% of the European Union’s total carbon emissions with cars and vans representing more than two thirds of this percentage. Therefore, vehicle electrification is of utmost importance to provide an alternative to fossil fuel driven (internal combustion engine) vehicles. Improved technology coupled with tightened emissions legislation has continuously driven costs of vehicle electrification down making electric vehicles more accessible. Battery electric vehicles mostly run on Lithium-ion batteries which have high battery capacity, very low memory effect and long lifetime. Battery Management Systems (BMS) primarily monitor lithium-ion cells for such parameters as voltage, current, temperature and battery states (e.g. state of; charge, health, function and power) to ensure that the batteries are safely utilised. Poor management of cell voltage, cell temperature or battery pack current damages the batteries and endangers the safety of vehicle users. The major aim of this project is to design and implement a Scalable Battery Management System (SBMS) for the scalable electric drivetrain of the Generation-3 car platform prototype at Infotiv AB, Gothenburg, that allows re-usability, reconfiguration and extension rather than redesign. In this thesis, we analyse the scalability aspects of modular electric vehicle BMSs and incorporating these aspects in designing a prototype SBMS. In order to ensure a fully scalable system implementation we apply design layering. In design layering, the scalability of the BMS design is studied in the topological, functional, hardware and software perspectives. In addition to technical aspects, we also analyse the cost implications of implementing such a system. A SBMS is implemented using a master microcontroller coordinating two module microcontrollers. Each module micro-controller controls a battery monitor, which in turn monitors eight cells. The layered design offers high flexibility not only in design and components, but also in cost estimation. The thesis is arranged as follows: it begins with introduction and theoretical sections, then design and implementation sections, and finally the analysis and conclusion sections.
Keywords: Electric Vehicle Batteries; Lithium Ion Battery Pack; Battery Management System; Cost Estimation; Scalability, Layered Design; Scalable Battery Pack; attery State Estimation; Modular Battery Topology